2021
DOI: 10.1523/eneuro.0265-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Consistency of Prior Movements Shapes Locomotor Use-Dependent Learning

Abstract: We would like to thank Margaret French for her helpful comments during phase 1 of this Registered Report and Simón Herrera Suarez for assistance with data processing. We would also like to thank the reviewers for their helpful comments during the phase 1 review process which motivated some of the model modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 65 publications
(109 reference statements)
8
15
0
Order By: Relevance
“…If so, the current results contrast somewhat with findings in sensorimotor adaptation (Huang et al, 2011;Shmuelof et al, 2012;Galea et al, 2015;Therrien et al, 2016) and use dependent learning (Floel et al, 2008;Mawase et al, 2017) in which reward boosts implicit aftereffects caused by other learning processes. However, the current results align with work suggesting that increased movement variability attenuates use-dependent learning (Verstynen and Sabes, 2011;Marinovic et al, 2017;Wood et al, 2021;Tsay et al, 2022). Indeed, when we match individuals across groups based on motor variability, the difference in implicit aftereffects disappears (n = 6 per group;…”
Section: Reinforcement Learning During Locomotion Is Accomplished By ...supporting
confidence: 89%
See 3 more Smart Citations
“…If so, the current results contrast somewhat with findings in sensorimotor adaptation (Huang et al, 2011;Shmuelof et al, 2012;Galea et al, 2015;Therrien et al, 2016) and use dependent learning (Floel et al, 2008;Mawase et al, 2017) in which reward boosts implicit aftereffects caused by other learning processes. However, the current results align with work suggesting that increased movement variability attenuates use-dependent learning (Verstynen and Sabes, 2011;Marinovic et al, 2017;Wood et al, 2021;Tsay et al, 2022). Indeed, when we match individuals across groups based on motor variability, the difference in implicit aftereffects disappears (n = 6 per group;…”
Section: Reinforcement Learning During Locomotion Is Accomplished By ...supporting
confidence: 89%
“…For comparison, we recruited a group that performed the same walking pattern using explicit, target error feedback, which does not induce significant exploration. Prior work has demonstrated that use-dependent learning is the predominant source of implicit aftereffects in this target error paradigm (Wood et al, 2021(Wood et al, , 2020, and neither implicit aftereffects nor explicit retention is contaminated by sensory prediction errors. We hypothesized that the reward prediction error group would learn the new walking pattern using greater exploration (a greater increase in motor variability above baseline), and that they would have larger implicit aftereffects and more accurate explicit retention compared to the target error group.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Repetition can bias future movements to resemble recently repeated ones [1], a phenomenon referred to as use-dependent learning (UDL). The effects of UDL can be seen in features such as the direction and speed of the current movement, and has been observed in movements ranging from single-joint actions to whole-body locomotion [2][3][4][5][6][7][8][9][10]. Theoretically, these movement biases have been attributed to shifts in the tuning of neurons towards the direction of a frequently practiced movement, a form of plasticity that alters the sensorimotor map underlying movement execution [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%